Elevated levels of PFOS and PFHxS in firefighters exposed to aqueous film forming foam (AFFF). (September 2015) - Rotander, Anna; Toms, Leisa-Maree L.; Aylward, Lesa; Kay, Margaret; Mueller, Jochen F.
Abstract: Exposure to aqueous film forming foam (AFFF) was evaluated in 149 firefighters working at AFFF training facilities in Australia by analysis of PFOS and related compounds in serum. A questionnaire was designed to capture information about basic demographic factors, lifestyle factors and potential occupational exposure (such as work history and self-reported skin contact with foam). The results showed that a number of factors were associated with PFAA serum concentrations. Blood donation was found to be linked to low PFAA levels, and the concentrations of PFOS and PFHxS were found to be positively associated with years of jobs with AFFF contact. The highest levels of PFOS and PFHxS were one order of magnitude higher compared to the general population in Australia and Canada. Study participants who had worked ten years or less had levels of PFOS that were similar to or only slightly above those of the general population. This coincides with the phase out of 3M AFFF from all training facilities in 2003, and suggests that the exposures to PFOS and PFHxS in AFFF have declined in recent years. Self-reporting of skin contact and frequency of contact were used as an index of exposure. Using this index, there was no relationship between PFOS levels and skin exposure. This index of exposure is limited as it relies on self-report and it only considers skin exposure to AFFF, and does not capture other routes of potential exposure. Possible associations between serum PFAA concentrations and five biochemical outcomes were assessed. The outcomes were serum cholesterol, triglycerides, high-density lipoproteins, low density lipoproteins, and uric acid. No statistical associations between any of these endpoints and serum PFAA concentrations were observed. Graphical abstract: Highlights: Elevated serum levels of PFOS and PFHxS in firefighters with past AFFF exposure. PFOS and PFHxS levels were positively associated with years of jobs with exposure. No associations between PFAA concentrations and biomarkers